2012
DOI: 10.1080/00103624.2012.641473
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Mineralization of Two Manures as Influenced by Contrasting Application Methods under Laboratory Conditions

Abstract: The decomposition and the associated nitrogen (N) dynamics of organic N sources are affected by their contact with soil. While several authors have examined the effect of surface application or incorporation of crop residues on their decomposition rate, less information is available about the relationship between the placement of animal manure and their N mineralization rate. This study investigated the influence of chicken manure and cattle manure placement on soil N mineralization. The manures were incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
(33 reference statements)
4
11
0
Order By: Relevance
“…This may suggest nitrification inhibition from treatments with feces of both diets (CT‐containing sainfoin and saponin‐containing alfalfa). Our results support other soil manure incubation studies showing initial immobilization of N with feces additions (Abbasi, Hina, Khalique, & Khan, 2007; Baitilwake et al., 2012; Probert, Delve, Kimani, & Dimes, 2005). Lower NO 3 in both feces treatments could be explained simply by fecal manure having more recalcitrant substrate which is digested (mineralized) more slowly, releasing available N more gradually.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This may suggest nitrification inhibition from treatments with feces of both diets (CT‐containing sainfoin and saponin‐containing alfalfa). Our results support other soil manure incubation studies showing initial immobilization of N with feces additions (Abbasi, Hina, Khalique, & Khan, 2007; Baitilwake et al., 2012; Probert, Delve, Kimani, & Dimes, 2005). Lower NO 3 in both feces treatments could be explained simply by fecal manure having more recalcitrant substrate which is digested (mineralized) more slowly, releasing available N more gradually.…”
Section: Resultssupporting
confidence: 91%
“…From the beginning (day 0) of the incubation study to the end (day 56), total N means in all treatments increased (p = .0003) from 1.10 to 4.26 mg g −1 , yet there were no differences between treatments (p = 1.0), nor interaction effects (p = .92). Our observed increase in N over the incubation study is consistent with other incubation studies (Abbasi et al, 2007;Baitilwake et al, 2012), showing an overall increase in total N.…”
Section: Laboratory Incubation Studysupporting
confidence: 93%
See 1 more Smart Citation
“…The observation that CHM led to more accumulation of nitrate in CC and AM than CAM at the first sampling could be explained by the slower release of N from CAM compared to CHM, as was observed in previous mineralization experiments under laboratory conditions (Baitilwake et al ., 2010). Indeed, the current results affirm further that N sources affect accumulation of nitrate in CC and AM plants at first sampling.…”
Section: Discussionmentioning
confidence: 99%
“…If the fertilizer is instead concentrated to narrow bands in the soil, microbial access to carbon and nitrogen, and thus nitrogen immobilization, will be more limited. Baitilwake et al (2012) found greater immobilization and nitrification after soil incorporation than surface application of chicken and cattle manure. However, Delin and Strömberg (2011) did not find any differences in net mineralization of nitrogen between surfaceapplied and incorporated chicken manure and cattle slurry, as long as the manure was kept in concentrated lumps, although when the manure was mixed with a larger soil volume both net immobilization and nitrification increased.…”
Section: Introductionmentioning
confidence: 99%